Clinical characteristics and plasma lipids in subjects with familial combined hypolipidemia: a pooled analysis - Minicocci, Ilenia (The American Society for Biochemistry and Molecular Biology, 2013)
Angiopoietin-like 3 (ANGPTL3) regulates lipoprotein metabolism by modulating extracellular lipases. Loss-of function mutations in ANGPTL3 gene cause familial combined hypolipidemia (FHBL2). The mode of inheritance and hepatic and vascular consequences of FHBL2 have not been fully elucidated. To get further insights on these aspects, we reevaluated the clinical and the biochemical characteristics of all reported cases of FHBL2. One hundred fifteen FHBL2 individuals carrying 13 different mutations in the ANGPTL3 gene (14 homozygotes, 8 compound heterozygotes, and 93 heterozygotes) and 402 controls were considered. Carriers of two mutant alleles had undetectable plasma levels of ANGPTL3 protein, whereas heterozygotes showed a reduction ranging from 34% to 88%, according to genotype. Compared with controls, homozygotes as well as heterozygotes showed a significant reduction of all plasma lipoproteins, while no difference in lipoprotein(a) [Lp(a)] levels was detected between groups. The prevalence of fatty liver was not different in FHBL2 subjects compared with controls. Notably, diabetes mellitus and cardiovascular disease were absent among homozygotes. FHBL2 trait is inherited in a codominant manner, and the lipid-lowering effect of two ANGPTL3 mutant alleles was more than four times larger than that of one mutant allele. No changes in Lp(a) were detected in FHBL2. Furthermore, our analysis confirmed that FHBL2 is not associated with adverse clinical sequelae. The possibility that FHBL2 confers lower risk of diabetes and cardiovascular disease warrants more detailed investigation.